ISOLATION OF BILE FROM FISH AND IDENTIFICATION BY THIN LAYER CHROMATOGRAPHY - MATHEW, P T; NAIR, K. G RAMACHANDRAN; MADHAVAN, P; PRABHU, P V (Fishery Technology, 2017)
The paper deals with the collection of gall bladders, isolation of bile and identification of the constituents of the bile salts from different fishes. The yield of bile contents from fresh water fishes rohu, mrigal and catla were compared with that from marine fishes seer, tuna, shark and sardine. Considerable variation in yield was showed between marine and fresh water fish as well as between the species in both groups. It ranged from 0.04 to 0.06% of the body weight of fish in calla, mrigal and rohu. The bile constituents from rohu and mrigal were analysed by thin layer chomatography. The result showed that bile of rohu and mrigal contains mainly taurine derivative of lithocholic acid